Respuesta :
y = 10x - 2
y = -7x + 3
10x - 2 = -7x + 3
10x + 7x = 3 + 2
17x = 5
x = 5/17
y = -7x + 3
y = -7(5/17) + 3
y = -35/17 + 3
y = -35/17 + 51/17
y = 16/17
solution is (5/17,16/17)
y = -7x + 3
10x - 2 = -7x + 3
10x + 7x = 3 + 2
17x = 5
x = 5/17
y = -7x + 3
y = -7(5/17) + 3
y = -35/17 + 3
y = -35/17 + 51/17
y = 16/17
solution is (5/17,16/17)
y = 10x - 2
y = -x + 3
Set the two equations equal to each other (as both equal y)
10x - 2 = -x + 3
Solve for x. Isolate the x.
10x (+x) - 2 (+2) = -x (+x) + 3 (+2)
10x + x = 3 + 2
11x = 5
Isolate the x. Divide 11 from both sides
11x/11 = 5/11
x = 5/11
Plug in 5/11 to one of the equations
y = -x + 3
y = -(5/11) + 3
y = -5/11 + 33/11
y = 28/11
x = 5/11, y = 28/11
hope this helps